A molecular-scale study on the role of lactic acid in new particle formation: Influence of relative humidity and temperature. (October 2017) - Li, Hao; Kupiainen-Määttä, Oona; Zhang, Haijie; Zhang, Xiuhui; Ge, Maofa
Abstract: It is well established that oxidation products of volatile organic compounds (VOCs) play a major role in atmospheric new-particle formation (NPF). However, the mechanism of their effect and the corresponding influence under various atmospheric conditions remain unclear. Meanwhile, considering the difficulty of experiment in determining the water content of the cluster and performing at low temperature, we combine Density Functional Theory (DFT) and Atmospheric Clusters Dynamic Code (ACDC) model to investigate a multicomponent system involving lactic acid (LA ) and atmospheric nucleation precursors (sulfuric acid (SA ), dimethylamine (DMA ), water (W )) under a wide range of atmospheric conditions (relative humidity ( RH ) from 20% to 100%, temperature ( T ) from 220 K to 300 K). Conformational analysis shows thatLA could enhance NPF in two direction due to its two highly oxidized function groups. Then, the results from ACDC simulation present a direct evidence of its enhancement effect on NPF when the concentration ofLA is larger than 10 10 molecules cm − 3 . The corresponding enhancement strength presents a positive dependence on its concentrations and a negative dependence on RH and T, respectively. Besides, LA ·nW (n = 0–1) reflect their enhancement effect on the cluster growth paths by acting as "bridge", which contributes to pureSA -DMA -W -based clusters by evaporatingLA contained clusters. The corresponding contribution presents a positive dependence on the concentration ofLA, RH and T, respectively. We hope our study could provide theoretical clues to better understand the characteristic of NPF in polluted area, where NPF commonly involves oxidized organics, sulfuric acid, amine and water. Graphical abstract: Highlights: The significant enhancement effect ofLA on NPF has been identified. The effect of atmospheric conditions onLA -contained system has been investigated. A "catalytic" enhancement mechanism ofLA· nW has been proposed.